Moving out of the silo: trialling a work-based education intervention to mobilise professional identity in integrated teams. Issue 2 (2nd February 2022) - Best, Stephanie; Beech, Christian; Fletcher-Miles, Hayley; Eynon-Jones, Sian; Robbé, Iain; Williams, Sharon
Abstract : Background/Aims: Research on professional identity has largely focused on students, with limited knowledge of how professional identity is mobilised among integrated team members, especially in relation to how this might be achieved through education and training. This study aims to trial a work-based education intervention to mobilise professional identity and gather feedback on the impact on healthcare practitioners. Method: This multi-method interventional study was centred around 2.5-hour workshops delivered for multidisciplinary teams, aiming to discuss and increase understandings of professional identity and its impact. Participants ( n =61) completed a pre-workshop survey to gauge their views of professional identity, teamwork and cognitive flexibility. Data from observation and workshop activities were recorded, and participants completed an evaluation survey at the end of the workshop to identify areas for improvement. Results: Participants generally welcomed the opportunity to discuss professional identity and the workshop was evaluated well overall. Most participants had a strong sense of professional identity. The design of the workshop needs to be reviewed to ensure that enough time is allowed for action planning. Conclusion: Managers need to identify opportunities to regularly discuss professional identity and identify the support required for new members of staff joining existing, well-formed integrated teams.